Data Visualization Shopping Trends XYZ Store Using Tableau - Winda Erika (Journal of Information Technology, computer science and Electrical Engineering, 2025)
The development of information technology encourages retail companies to utilize data in business decision-making. XYZ Store, as a retail business player, has sales transaction data that has the potential to provide important insights regarding customer shopping patterns. This study aims to visualize XYZ Store's shopping trends using Tableau as a business intelligence tool. The methods used include collecting sales transaction data, cleaning and processing data, and presenting data in the form of interactive visualizations. The resulting visualizations include sales trends based on time, product category, location, and customer behavior. The results show that the use of Tableau can help identify sales patterns, peak sales periods, and products that are most in demand by customers. With informative and easy-to-understand data visualizations, XYZ Store management can make strategic decisions more effectively and based on data.